Integration of DevOps Practices on a Noise Monitor System with CircleCI and Terraform - Romero, Esteban Elias; Camacho, David; Montenegro, Carlos Enrique; Acosta Agudelo, Oscar Esneider; González-Crespo, Rubén; Gaona-García, Elvis; Herrera Martínez, Marcelo (ACM Transactions on Management Information Systems, 2023)
Lowering pollution levels is one of the main principles of Sustainable Development goals dictated by the United Nations. Consequently, developments on noise monitoring contribute in great manner to this purpose, since they give the opportunity to governments and institutions to maintain track on the matter. While developing a software product for this purpose, with the growth in terms of functional and non-functional requirements, elements such as infrastructure, source code, and others also scale up. Consequently if there are not good practices to face the new challenges of the software product, then it could become more complex to refactor, maintain, and scale, causing a decrease on delivery rate and the quality of the product. DevOps is an emerging concept but still hazy, which involves a set of practices that helps organizations to speed up delivery time, improve software quality and collaboration between teams. The aim of this article is to document the implementation of some DevOps practices such as IaC, continuous integration and deployment, code quality control, and collaboration on a noise monitor system to increase the product quality and automation of deployment. The final result is a set of automated pipelines that represents the entire integration and deployment cycle of the software integrated with platforms to improve quality and maintainability of the software components.
Keywords: CI/CD; classification; DeVOps; serverless; sound; Scopus; Emerging